Ludovico Quaroni is a super Venturi? (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Reading Housing and the city. LOVE vs HOPE, I was very happy to follow several examples from the Italian scene, and in particular by the presence of the urban development of Casilino in Rome, that was designed and coordinated by Ludovico Quaroni, but it was never at the center of the Italian debate on the topic. Other than Robert Venturi! The real genius of “Complexity and contradictions” was our Ludovico Quaroni. Who knows him, knows... his beginnings in Piacentini style, the opposite Neorealism of his Tiburtino and La Martella Villages which he refused in his churches, beautiful and massive.